Effect of Glutaraldehyde on Dentin Hypersensitivity after Non-surgical Periodontal Therapy: A Randomized, Triple-blinded Clinical Study - Silva, Fábio Alves; Barros, Antonia Patricia Oliveira [UNESP]; Alencar, Cristiane de Melo; Carneiro, Alexandra Melo Pingarilho; Silva, Cecy Martins (Bentham Science Publishers, 2023)
Aims and Objectives: The purpose of this study was to evaluate the effect of 5% glutaraldehyde (5% Gluma), in association with 37% phosphoric acid conditioning, on dentin hypersensitivity (DH) after non-surgical periodontal treatment (NSPT). Additionally, we investigated the impact of these treatments on health-related quality of life (HRQoL). Methods: Ninety hypersensitive teeth of subjects were randomized into the following three groups based on treatment (n = 30): GP: placebo gel that simulates 37% phosphoric acid (37% PA) + distilled water, GPG: placebo gel that simulates 37% PA + 5% Gluma, and GAG: 37% PA + 5% Gluma. Two visual analog scales (VASs) were used to measure DH after tactile and evaporative stimulation four times. The HRQoL was recorded using a DH experience questionnaire (DHEQ). Statistical analysis of DH data was performed using Friedman vs. Kruskal-Wallis tests. DHEQ data were analyzed using Wilcoxon vs. Mann–Whitney tests and a simple logistic regression (α= 0.05). Results: The GPG and GAG groups showed significantly lower DH than GP (p ≤ 0.05) for tactile and evaporative stimulations. After one month of follow-up, the GPG and GAG groups showed an increase in HRQoL, which was higher than that of the GP group (p ≤ 0.05). Gluma (5%) effectively prevented DH for up to 15 days after NSPT, regardless of previous conditioning with phosphoric acid. In addition, treatment with 5% gluma had a positive impact on HRQoL. Conclusion: The treatment with 5% glutaraldehyde was effective in HD and had a positive impact on quality of life.
Keywords: Dental scaling; Dentin desensitizing agents; Dentin sensitivity; Dentistry; Randomized controlled trial; Treatment